Adoption of emicizumab (Hemlibra®) for hemophilia A in Europe: Data from the 2020 European Association for Haemophilia and Allied Disorders survey. Issue 5 (30th June 2021) - Krumb, Evelien; Fijnvandraat, Karin; Makris, Michael; Peyvandi, Flora; Ryan, Aislin; Athanasopoulos, Angelos; Hermans, Cedric
Abstract: Background: Emicizumab, a bispecific monoclonal antibody administered subcutaneously, mimicking the action of activated coagulation factor VIII, has been approved in Europe for use in patients with severe hemophilia of all ages. Aims: To assess availability, acceptance, adverse events, efficacy and laboratory monitoring of emicizumab and the effect of the coronavirus disease 2019 (COVID‐19) pandemic on its use. Methods: Online questionnaire sent to 144 hemophilia treatment centres (November 2020 to January 2021). Results: Forty‐six physicians from 21 countries responded, with a total of 3420 patients with severe HA under their care. Emicizumab was widely available, for 100% of inhibitor patients and 88% of non‐inhibitor patients. No major adverse events were reported. Four reported deaths in patients on emicizumab were not thought to be related to emicizumab. An annualized bleeding rate (ABR) of zero was achieved in 73% of inhibitors patients. Haemostasis was satisfactory in the majority of minor (93.7%) and major (90.7%) surgical procedures performed while on emicizumab. Inhibitor titers were monitored in 78.4% of inhibitor patients on emicizumab, but chromogenic FVIII assay was only available in 73% of centres. The COVID‐19 pandemic did not have a major impact on the adoption of emicizumab in most centres (64.9%). Conclusion: Three years after its rollout in Europe, emicizumab is widely available. Clinical efficacy and safety were evaluated to be very good, keeping in mind the inherent limitations of the study. Unmet needs include establishment of treatment guidelines for surgery and breakthrough bleeding, limited expertise, especially in young children, and availability of laboratory assays.